(untitled) (Oxford, 1995)
Sucessive editions of this remarkable work have facilitated international trade in fish and fish products by making available a comprehensive source of specialised information and general knowledge on fish, other marine life, and fish products in commercial use today.
Keywords: Fishes,Fishery products,Dictionaries, Polyglot; Polyglot,Polyglot